The biosphere (Chicago : CyberEd, 1999)
This interactive educational program includes presentation with automatic/manual user control, includes integrated animations, custom graphics, jump presentation menu, pre- and post testing, online interactive glossary and also online interactive help
Systems requirements : IBM-Compatible PC, 4 MB available RAM memory (8MB or higher), hard disk space 256k,Windows 3.1, 95 or higher, S-VGA graphics, CD-ROM drive (2x speed preferred)
Keywords: Biosphere